The Relationship between the Incidence of Acute Otitis Media in Patients with Upper Respiratory Tract Infections at PKU Muhammadiyah Yogyakarta Hospital - Harisna, Safyra Putri; Abdullah, Adnan; Prisilla, Elvina (Universitas Ahmad Dahlan, 2023)
Acute Otitis Media (AOM) is an inflammation of the middle ear caused by blockage of the Eustachian tube, impaired immune factors, and recurrent Upper Respiratory Tract Infections (URTI). The highest incidence of AOM can be found in developing countries. Among the numerous cases, 70% of AOM cases begin with a history of URTI. As a result of URTI history, congestion, and swelling occur in the nasal mucosa, nasopharynx, and eventually the Eustachian tube, leading to the development of AOM symptoms. The purpose of this study is to determine the relationship between the occurrence of acute otitis media and patients with upper respiratory tract infections at PKU Muhammadiyah Yogyakarta Hospital. This study is descriptive-analytical quantitative research with a cross-sectional design and retrospective study. Data collection was conducted through the collection of secondary data obtained from medical records of otitis media patients. This research was conducted from November to December 2022 at PKU Muhammadiyah Yogyakarta Hospital. The research subjects consisted of 113 individuals with otitis media. This study reports the analysis of the relationship between the occurrence of acute otitis media and patients with upper respiratory tract infections. There is no significant relationship between AOM and URTI among patients at PKU Muhammadiyah Yogyakarta Hospital, with a p-value of 0,457. There is no relationship between the occurrence of acute otitis media and patients with upper respiratory tract infections at PKU Muhammadiyah Yogyakarta Hospital.